Mesoporous TUD-1 supported indium oxide nanoparticles for epoxidation of styrene using molecular O21. Issue 58 (25th June 2015) - Rahman, Sumbul; Farooqui, Saleem A.; Rai, Aditya; Kumar, Rawesh; Santra, Chiranjit; Prabhakaran, Vinod C.; Bhadu, Gopala Ram; Sen, Debasis; Mazumder, S.; Maity, Sudip; Sinha, Anil K.; Chowdhury, Biswajit
<x xml:space="preserve">Abstract</x> Activation of molecular O2 by metal or metal oxide nanoparticles is an area of recent research interest.